2016
DOI: 10.4103/0971-4065.158449
|View full text |Cite
|
Sign up to set email alerts
|

Validity of nutrition risk index as a malnutrition screening tool compared with subjective global assessment in end-stage renal disease patients on peritoneal dialysis

Abstract: We undertook this study to compare subjective global assessment (SGA) and nutrition risk index (NRI) as malnutrition screening tools in peritoneal dialysis (PD) patients. Nutrition status of the patients was categorized into low, moderate and high risk of malnutrition based on both NRI and SGA. The sensitivity, specificity and predictive values of NRI were compared with SGA, an already validated tool of nutrition status assessment in PD patients. Two hundred and eighty-three end-stage renal disease patients (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
1
23
2
3
Order By: Relevance
“…Given that most of stroke patients are over 60 years old and have underlying disease, the use of GNRI for stroke patients is worth considering. In another aspect, the GNRI has a high sensitivity for malnutrition compared to other reliable assessment tools [22]. Approximately 20% of the stroke patients had a moderate or severe risk of malnutrition at admission in our study based on the GNRI result, which was within the range reported previously [23].…”
Section: Discussionsupporting
confidence: 79%
“…Given that most of stroke patients are over 60 years old and have underlying disease, the use of GNRI for stroke patients is worth considering. In another aspect, the GNRI has a high sensitivity for malnutrition compared to other reliable assessment tools [22]. Approximately 20% of the stroke patients had a moderate or severe risk of malnutrition at admission in our study based on the GNRI result, which was within the range reported previously [23].…”
Section: Discussionsupporting
confidence: 79%
“…However, when considering other studies, the prevalence of malnutrition by MIS in our population is similar to that reported in the literature (20). The prevalence of malnutrition diagnosed by BIVA was 24%, which is lower than that found in other studies with different diagnostic tools (18)(19)(20)(21). To our knowledge, there is no other study that has made the diagnosis of malnutrition using impedance vectors, so we cannot know if the prevalence reported here is similar to that of other populations.…”
Section: Discussioncontrasting
confidence: 53%
“…In this study we found a prevalence of malnutrition diagnosed by MIS of 38%, considerably lower than that found by Singh et al (18) in Malaysia and Prasad et al (19) in India, where the prevalence of malnutrition reached 90% and 74.9%, respectively. However, when considering other studies, the prevalence of malnutrition by MIS in our population is similar to that reported in the literature (20).…”
Section: Discussioncontrasting
confidence: 52%
“…20 It can be used as screening tool but not as a diagnostic tool for assessment of nutritional status in peritoneal dialysis patients because of its low specificity and NPV.…”
Section: Discussionmentioning
confidence: 99%